An Error Analysis of EFL Undergraduate Students’ Writing Composition in Universitas Tanjungpura - Rahmani, Eka Fajar (FKIP Universitas Lampung, 2023)
An error analysis of EFL undergraduate student’ writing composition. This study has thoroughly investigated morpho-syntactic errors in the compositions of English Language Education undergraduates at Universitas Tanjungpura. Employing a descriptive methodology and drawing from Ellis (1994), the research analyzed 97 self-descriptive compositions. The findings reveal a significant prevalence of morpho-syntactic errors, totaling 793 syntactical and 333 morphological errors across an average of 18 sentences per composition. Syntax errors involve sentence patterns and subject-verb agreement, while morphological errors revolve around inflection and conversion challenges. Categorized into omissions, additions, misinformations, and misorderings using a surface strategy taxonomy, the errors provide insights into students' linguistic competence. The study advocates for targeted instructional interventions, integrated curriculum development, cross-linguistic awareness programs, and learner-centered approaches. Longitudinal studies and teacher training programs are recommended for a deeper understanding of error evolution and effective pedagogical implementation, contributing to the discourse on morpho-syntactic errors in EFL writing with practical implications for language instruction. Keywords: Error analysis, morpho-syntactic error, self-descriptive compositionDOI: http://dx.doi.org/10.23960/jpp.v13.i3.202331